HUMANISTIK DALAM PIDATO PERDANA KHALIFAH UMAR BIN KHATTAB "KAJIAN HERMENEUTIK" - Abu Bakar Shiddiq (Jurnal Ilmu dan Budaya, 2020)
This paper analyzes humanistic values in Umar bin Khattab's first sermon in his caliphate by using Hermeneutic analysis to interpret a text of Umar bin Khattab's speech and can be understood. The stages carried out are three stages, namely understanding, interpretation, and application in real life. Humanistic in question is the values of humanity that exist and feel necessary to be conveyed in a broader and more comprehensive scope by using heurmentic studies so that an assessment of the content of humanistic values and messages that existed and was acceptable at that time could also turned on and adapted so that it becomes a value that is acceptable and in accordance with the conditions of society and reality that exists in this era so that later these humanistic values can change the morals, ethics and culture of humans at this time into a better, wise and perfect human figure.